Sepsis: Changing Definitions, Unchanging Treatment - Obonyo, Nchafatso Gikenyi; Schlapbach, Luregn Jan; Fraser, John Francis (Frontiers in Pediatrics, 2019)
The recently revised Sepsis-3 definitions were based on criteria that were derived and validated in adult patient databases from high income countries. Both sepsis and septic shock continue to account for a substantial proportion of mortality globally, especially amongst children in low-and-middle income country settings. It is therefore urgent to develop and validate standardised criteria for sepsis that can be applied to paediatric populations in different settings, including in- and outside intensive care, both in high- and low/middle- income countries. This will be a pre-requisite to evaluate the impact of sepsis treatment strategies to improve clinical outcomes.